Mechanical flexure behavior of bio-inspired collagen-reinforced thin composites. (1st October 2016) - Sharabi, Mirit; Varssano, David; Eliasy, Rami; Benayahu, Yehuda; Benayahu, Dafna; Haj-Ali, Rami
Abstract: Soft tissue can be viewed as a multi-layered composite structure reinforced with different collagen fiber systems used to control the overall mechanical properties. The objective of this study was to manufacture, test and model the mechanical behavior of a multidirectional collagen reinforced composite material system. To that end, novel bio-composite constructs were fabricated from long collagen fibers reinforced polyacrylamide–alginate (PAAm–Alg) matrix. The collagen fibers were aligned in multi-directions within thin circular matrix plates. The constructs were clamped and subjected to flexure using a rigid spherical indenter. Three dimensional finite element (FE) models were generated with continuum and beam elements representing the matrix and fibers, respectively. The hyperelastic behavior predicted by the calibrated FE models was validated based on the results of one tested configuration. The new bio-inspired composites can be tailored to generate similar mechanical behavior of native tissues. The FE model can be employed to design future complex constructs for soft tissue substitutes.